DAMPAK PENURUNAN HARGA BELI GULA PADA PETANI TEBU DI KABUPATEN PROBOLINGGO - Bethari Brilianti; Lenny Widjayanthi (UNEJ e-Proceeding, 2018)
In May 2017, the government issued the fixed price of staple food, one of them was sugar which experienced a decrease in the highest retail price (HET) and affect the purchase price of sugar at the level of sugarcane farmers from Rp. 11,000 per kilogram to Rp. 9,700 per kilogram. The purpose of the study was to find out the impact of the decrease of the purchased price of sugar at the farmers level. Purposive method was applied to determine the study area, namely in Probolinggo. the research informants was choosen purposivly by conducting the depth interview to three respondents, they are APTR, KPTR and sugarcane farmers in Probolinggo. The data analysis used the Miles and Huberman model and the data validity used triangulation of sources of informant and interview techniques. The result shows that (1) the social impact due to a decrease in the purchased price of sugar at the farmers level is a change in the cultivation technique of sugarcane, the interaction between farmers and APTR and the interaction between APTR and the government; (2) the economic impact due to the decrease in the purchased price of sugar at the farmers level of sugarcane is a decrease in the income of sugarcane farmers and how to anticipate the management of sugarcane cultivation.